2014
DOI: 10.7205/milmed-d-14-00169
|View full text |Cite
|
Sign up to set email alerts
|

Heat Tolerance Testing: Association Between Heat Intolerance and Anthropometric and Fitness Measurements

Abstract: This study investigated associations between heat intolerance, as determined by performance on a heat tolerance test (HTT), and anthropometric measurements (body surface-to-mass ratio, percent body fat, body mass index, and waist circumference) and cardiorespiratory fitness (maximal oxygen uptake [VO2max]). Relationships between predictive variables and specific physiological measurements recorded during the HTT were examined. A total of 34 male and 12 female participants, recruited from the military community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 39 publications
3
66
3
Order By: Relevance
“…The HTT has been in use by the IDF since 1983 and the investigators have suggested that it is useful and effective for identifying heat intolerance (Kazman et al 2013;Lisman et al 2014;Moran et al 2007). Soldiers who passed the HTT and fully resumed duty reportedly did not suffer a subsequent bout of heat injury (Epstein and Heled 2013;McDermott et al 2007).…”
Section: Militarymentioning
confidence: 99%
See 3 more Smart Citations
“…The HTT has been in use by the IDF since 1983 and the investigators have suggested that it is useful and effective for identifying heat intolerance (Kazman et al 2013;Lisman et al 2014;Moran et al 2007). Soldiers who passed the HTT and fully resumed duty reportedly did not suffer a subsequent bout of heat injury (Epstein and Heled 2013;McDermott et al 2007).…”
Section: Militarymentioning
confidence: 99%
“…Several researchers also recommend using the HTT to assist in return-to-duty/play decisions for post heat-illness individuals (Kazman et al 2013;McDermott et al 2007;O'Connor et al 2007). Yet, the United States military does not adopt the HTT for this purpose (Kazman et al 2013;Lisman et al 2014). The validity of the HTT has also been questioned (Johnson et al 2013;O'Connor et al 2010).…”
Section: Militarymentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the test really does not assess "tolerance" as the cardiovascular and core temperature responses represent a compensable or plateau response to the exercise and heat stress. Those that are identified as "intolerant" have a lower level of aerobic fitness and higher body fatness (Lisman et al 2014), and many would probably not be successful during the current PES testing. Instead, the heat tolerance test should create an uncompensable condition, which is more typically associated with wearing PCE, where core temperature and heart rate would continue to increase with continued exposure to the exercise and hot conditions.…”
Section: Protective Clothing and Aerobic Fitnessmentioning
confidence: 99%